Total Ionizing Dose Effects in MOS and Low-Dose-Rate-Sensitive Linear-Bipolar Devices - Fleetwood, D. M. (IEEE transactions on nuclear science, 2013)
An overview is presented of total ionizing dose (TID) effects in MOS and bipolar devices from a historical perspective, focusing primarily on work presented at the annual IEEE Nuclear and Space Radiation Effects Conference (NSREC). From the founding of the IEEE NSREC in 1964 until ~1976, foundational work led to the discovery of TID effects in MOS devices, the characterization of basic charge transport and trapping processes in SiO 2 , and the development of the first generations of metal-gate radiation-hardened MOS technologies. From ~1977 until ~1985, significant progress was made in the understanding of critical defects and impurities that limit the radiation response of MOS devices. These include O vacancies in SiO 2 , dangling Si bonds at the Si/SiO 2 interface, and hydrogen. In addition, radiation-hardened Si-gate CMOS technologies were developed. From ~1986 until ~1997, a significant focus was placed on understanding postirradiation effects in MOS devices and implementing hardness assurance test methods to qualify devices for use in space systems. Enhanced low-dose-rate sensitivity (ELDRS) was discovered and investigated in linear bipolar devices and integrated circuits. From ~1998 until the present, an increasing focus has been placed on theoretical studies enabled by rapidly advancing computational capabilities, modeling and simulation, effects in ultra-thin oxides and alternative dielectrics to SiO 2 , and in developing a comprehensive model of ELDRS.